TERRAÇO CAPIXABA: ESTRATÉGIA PASSIVA FRENTE ÀS MUDANÇAS CLIMÁTICAS - Ferrao, Ariane Louzada Sasso (2022)
The research analyzed different roof system in relation to thermal performance in the current climate condition, and two different roof system in the future climate condition of high emission of greenhouse gases, in a hot and humid region, under stress caused by the absence of ventilation; considering in the analyzes the use of Terraço Capixaba (TC) as a passive strategy to improve the thermal performance during the useful life (VU) of Brazilian buildings. Through the computational simulation methodology of NBR 15575/2021, was possible to perceive the terraço capixaba as an efficient and resilient system for the climate of the study, up to half a VU of buildings exposed to the conditions of the study, considering the continuity of the climate change process, and, in addition, the methodological process developed during the research allowed identifying the difficulty for buildings to reach intermediate and superior levels in regions with unfavorable ventilation conditions. The investigative methodology was developed in five stages: Stage 1: which dealt with the justification for choosing and characterizing the study area; stage 2: observation survey; step 3: modeling; step 4: thermal evaluation; step 5: thermal evaluation in future scenarios. The results pointed to the ability of roofing systems of the terraço capixaba contributes to the improvement of the thermal performance of buildings, in the climate conditions of the sample cutout, until the proximity of the 2050’s with the continuity of the climate change process, and the tendency to become unable to continue contributing later. Secondarily, the analyzes indicated weaknesses in the criterion for defining operating temperature ranges (FT) of the NBR 15575/2021 methodology, based exclusively on the dry bulb temperature (TBS) of climate files, without considering other climate variables. In addition, was observed that the way used to define the FT, which are defined considering parameters of adaptive comfort, can mask the performance results, giving to a worse performance level to a reference-modelreal-model relationship a higher performance level, and to a better model-reference-model-real relationship, less high performance, and with greater difficulty in climbing levels above the minimum, which occurs exclusively due to the FT used in the analysis, and the dependence on wind conditions capable of dissipating heat in the built environment, which tends to obsolescence in several regions of the country with the continuity of the climate change process.